Pengaruh Profitabilitas, Solvabilitas, dan Ukuran Perusahaan terhadap Audit Delay: Studi pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2017–2024 - Pratiwi, Ihsani Dwi; Damayanti, Santi (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
This study aims to analyze the influence of profitability, solvency, and company size on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017–2024 period. This study employs a quantitative approach, utilizing secondary data obtained from the annual financial reports of six pharmaceutical companies. The analytical method used is panel data regression with the Fixed Effects Model (FEM) approach, following a series of model selection tests, including the Chow, Hausman, and Lagrange Multiplier tests. The results indicate that profitability, as measured by Return on Assets (ROA), has a negative and statistically significant effect on audit delay. Solvency, proxied by the Debt-to-Equity Ratio (DER), has a positive and significant impact on audit delay. Meanwhile, company size, proxied by the natural logarithm of total assets, has no significant effect on audit delay. The adjusted R-squared value of 0.592 indicates that the three independent variables explain 59.2% of the variation in audit delay. These findings have implications for company management, auditors, and regulators in improving the timeliness of financial reporting and maintaining transparency in the capital market.